Kaji Eksperimental Kekuatan Briker Hasil Reduksi Bijih Besi Dengan Batubara Muda Menggunakan Metode Hot Briquetted Iron (HBI) - Khairil Khairil; Sarwo Edhy Sofyan; Andre Adhitya (Jurnal Teknik Mesin Unsyiah, 2020)
This research aims to study the mechanics (strength) properties of iron ore briquettes. Iron ore briquettes are made using the hot briquetted iron method (HBI). HBI is a briquette after reduction directly and pressed at a temperature above 650 ⁰C and has more density than 5000 kg/m3. The specimens used were iron ore briquettes made of the composition of iron ore, coal, and adhesives. The composition of the briquettes is 55: 40: 5, 65: 30: 5, 75: 20: 5, 85:10: 5 and the reduction temperature is 750⁰C,850⁰C,950⁰C and 1050⁰C. There are 16 briquett specimens. After the briquettes are made, the briquettes are reduced using a reduction blast furnance which is fuel by LPG and CO2 gas. When the mass of briquette is no longer decrease ore the time (reach steady state condition) the briquettes take out from the blast furnance for press. Pressing is carried out in hot briquettes conditions and the press load is 15 tons. The results obtained from testing the I-Type Tumbler Test have more small paricle ruptures because the briquettes have lost their adhesive during the reduction process and coal does not affect the strength of the HBI briquettes. After being reduced briquettes are given more adhesive so that briquettes can be tested again. Iron ore briquettes after reduction are stroger than those before reduction. In the variation 85:10:5 obtained from testing I-Type Tumbler Test iron ore briquettes test after reduction has a number of particle small rupture 0,21% while iron ore briquettes before reduction of 3,35%.